Feature selection in small databases: A medical-case study - Soares, Inês (2021)
Predictions made by using machine learning classification models are recurrent in many research fields for a variety of reasons. In some cases, feature selection can effi- ciently improve the accuracy of classifications, while reducing the computational requirements. However, some predictive studies are characterized by a high dimensionality or based on small datasets.